STRUKTUR DAN PERAN SEMANTIK VERBA MEMOTONG DALAM BAHASA INGGRIS: PENDEKATAN METABAHASA SEMANTIK ALAMI - Dewa Ayu Dyah Pertiwi Putri (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The article aimed at investigating and mapping the semantic structures and roles of English verb belonging to the concept of cutting. The data were collected from both English articles and videos by combining comprehending and note taking methods. The collected data were analyzed by applying the Theory of Natural Semantic Metalanguage and Semantic Macro Role. The results showed that there were 11 lexicons (slice, mince, dice, julienne, chiffonade, fillet, trim, clip, snip, mow, and hew) reffering to the cutting concept, which were varied based on the aim, the instrument, the method, the entity and the result of which the cutting concept was implemented. Further, English cutting verb was uncovered to merge some arguments which were agent, patient, theme, instrument, benefactive, source, time, and location.